Effects of siblings and birth order on income redistribution preferences: Evidence based on Japanese General Social Survey - Eiji Yamamura (Economics and Econometrics Research Institute (EERI), 2012)
The Japanese General Social Survey was used to determine how individual preferences for income redistribution are affected by family structure, such as the number of siblings and birth order where individuals grow up. After controlling for various individual characteristics, the important findings were as follows. (1) The first-born child was less likely to prefer income redistribution when the child was male. However, such a tendency was not observed when the child was female. (2) The larger the number of elder brothers, the more likely an individual preferred income redistribution. However, the number of elder sisters did not affect the preference. (3) The number of younger siblings did not affect the preference for redistribution regardless of the sibling's sex. These findings regarding the effect of birth order are not consistent with evidence provided by another study conducted in a European country.
Keywords: D19; D30; D63; J13; 330; Inequality aversion; Redistribution; Family structure; Birth order; Siblings